FORMATION OF COMPETENCES OF STUDENTS OF TECHNICAL SPECIALTIES IN THE PROCESS OF THEIR FUNDAMENTAL MATHEMATICAL TRAINING - Kolomiiets, Alona; Klochko, Vitalii; Stakhova, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The classification of competences of graduates of secondary and higher technical educational establishments is presented in the work. On the basis of the list of professional and mathematical competences offered by scientists, the professional-oriented mathematical competences of the future specialist, the most important and relevant for the professional activity of future engineers, are allocated. These include: conceptual, operational-algorithmic, applicable, design.The purpose of the article is to describe an experimental verification of the professionally-oriented mathematical competencies formation of future specialists in the electronics and telecommunications industry. The main research methods used by the authors: theoretical methods: analysis, synthesis, comparison and generalization of the research results of scientific and methodological literature on selected issues; empirical: observation, experiment, questionnaire, analysis of the obtained test results. During the study of higher mathematics, students are encouraged to take actions that promote the formation of skills that are part of mathematical competences. These actions are also performed by the engineer, he also needs to be able to analyze, synthesize, classify. Therefore, the formation of the above mathematical competences is appropriate and necessary for the professional training of the engineer.